Drug-induced prolonged corrected QT interval in patients with methadone and opium overdose - Davood Soroosh; Mahbubeh Neamatshahi; Bahram Zarmehri; Samaneh Nakhaee; Omid Mehrpour (BMC, 2019)
Abstract Background Iran is a country with the highest rate of opioid addiction in the world. The most commonly used opioid in Iran is opium, and methadone is in second place. The trend of drug use has changed from opium to methadone from 2006 to 2011. Presence of a large number of addicted people and methadone maintenance therapy clinics make methadone readily available in Iran. Therefore, evaluation of the epidemiological characteristic of methadone toxicity and its effects on the heart is essential. Methods In This cross-sectional, retrospective, descriptive, analytical study all patients with methadone or opium toxicity who had been admitted to Vasei hospital, Sabzevar, Iran, during the years 2015 and 2016 were included, and their records were evaluated. Demographic data, addiction history, underlying diseases, and the outcome of admission were recorded. Then, corrected QT interval (QTc) of the first ECG of the patients after admission was evaluated. Results The Majority of toxicities occurred in those above 30 years of age (71.4%), who lived in cities (62.8%), and were married (69.2%). A positive history of addiction was considerably higher in the opium group (72.3% versus 43.3%). There was no significant difference regarding QTc prolongation between patients with methadone and opium toxicity (p = 0.3). Conclusion QTc prolongation is one of the adverse effects of methadone or opium overdose. It seems that significant QTc prolongation is not uncommon among patients with opium overdose.